C8–H bond activation vs. C2–H bond activation: from naphthyl amines to lactams. Issue 90 (26th October 2016) - Shi, Renyi; Lu, Lijun; Xie, Hangyu; Yan, Jingwen; Xu, Ting; Zhang, Hua; Qi, Xiaotian; Lan, Yu; Lei, Aiwen
Abstract : Pd-catalyzed selective amine-oriented C8–H bond functionalization/ N -dealkylative carbonylation of naphthyl amines has been achieved. The amine group from dealkylation is proposed to be the directing group for promoting this process. It represents a straightforward and easy method to access various biologically important benzo[ cd ]indol-2(1 H )-one derivatives. Abstract : Pd-catalyzed selective amine-oriented C8–H bond functionalization/ N -dealkylative carbonylation of naphthyl amines has been achieved. The amine group from dealkylation is proposed to be the directing group for promoting this process. It represents a straightforward and easy method to access various biologically important benzo[ cd ]indol-2(1 H )-one derivatives.